2014
DOI: 10.1017/s0950268814003136
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of interview methods to ascertain fluoroquinolone exposure before tuberculosis diagnosis

Abstract: Summary Fluoroquinolone use before tuberculosis diagnosis delays the time to diagnosis and treatment, and increases the risk of fluoroquinolone-resistant tuberculosis and death. Ascertainment of fluoroquinolone exposure could identify such high-risk patients. We compared four methods of ascertaining fluoroquinolone exposure in the six months prior to tuberculosis diagnosis among culture-confirmed tuberculosis patients in Tennessee from January 2007 through December 2009. The four methods included a simple ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A study conducted in Alberta, Canada, found that 17% of newly diagnosed TB patients had received one or more FQ prescriptions in the 6 months preceding their diagnoses (27). This likely led to periods of FQ monotherapy of their yet-undiagnosed TB, which can drive the emergence of FQ-resistant M. tuberculosis (28). Although previous reports, including this Canadian study, have shown that a single course of FQ is not associated with increased risk of FQresistant TB (26,27), our genomic study suggests that this observation may be ignoring the existence of undetected low-frequency resistant subpopulations that could lead to FQ treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Alberta, Canada, found that 17% of newly diagnosed TB patients had received one or more FQ prescriptions in the 6 months preceding their diagnoses (27). This likely led to periods of FQ monotherapy of their yet-undiagnosed TB, which can drive the emergence of FQ-resistant M. tuberculosis (28). Although previous reports, including this Canadian study, have shown that a single course of FQ is not associated with increased risk of FQresistant TB (26,27), our genomic study suggests that this observation may be ignoring the existence of undetected low-frequency resistant subpopulations that could lead to FQ treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…Three of these resistant isolates were among the 111 clinical isolates which were fully susceptible to the first-line anti-TB drugs isoniazid, rifampin, and ethambutol. This shows that FQ monoresistance is a problem in Iran that risks the efficient treatment of MDR-TB due to the overuse of this drug for the treatment of community-acquired pneumonia and other bacterial diseases, as well as the treatment of non-TB respiratory symptoms [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Since FQs have broadspectrum activity, they are usually overprescribed for various other bacterial infections, and they are easily accessible as over-the-counter medications in many resource-limited countries, exacerbating their misuse [18,20]. This has led to the increased emergence of FQresistant M. tuberculosis strains [21,22]. Resistance can also be developed due to the incomplete adherence to the TB treatment program, failure in previous treatment and contact with patients of resistant tuberculosis [18].…”
Section: Introductionmentioning
confidence: 99%